Cytogenetic studies of Pseudobarbus and selected Barbus (Pisces: Cyprinidae) of southern Africa - Naran, Daksha (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1997)
The aim of this study was to explore the karyology of temperate southern African barbine species in order to determine the extent and significance of polyploidy within the species. The study presents an optimised in vivo karyological protocol for the small barbines. The analysis of chromosomal data was explored using two approaches; measured (quantitative) and visual (qualitative). The karyology of 16 species of Barbus and six species of Pseudobarbus (Pisces: Cyprinidae) is reported. The study represents an almost complete (22/23 species) karyological survey of the temperate barbines. Chromosome number, arm numbers (NF) are recorded and karyotype morphology described for all species. Nucleolar organiser regions (NOR)s of 18 species have been examined by silver staining. Seven different AgNOR phenotypes occur among the species examined. Chromosome complements of the different species indicate at least three ploidy levels; diploid, tetraploid and hexaploid. Higher ploidy levels are represented in 78% (18/23) of species within the temperate fauna. This finding is remarkable, in the light of global proportions of cyprinid karyotypes, and provides an opportunity to shed further light on the evolution of polyploidy in barbine cyprinids. Results show that morphologically defined species complexes have distinct karyotypes, and most probably form cohesive phyletic clades. A phylogenetic tree was constructed using traditional morphological characters and tested against karyological data. The results suggests that similar ploidy states do not necessarily indicate close relationship between species. This supports a hypothesis of polyphyly for the African barbine cyprinids and also provides independent support for species complexes such as the "chubbyhead barb group" and the Pseudobarbus lineage. The broader implications of karyological findings are discussed within the context of African barbines and recommendations for further cytogenetic research are provided.
Keywords: Cyprinidae